Sanse Powder Essential Oil Nanoemulsion Negatively Regulates TRPA1 by AMPK/mTOR Signaling in Synovitis: Knee Osteoarthritis Rat Model and Fibroblast-Like Synoviocyte Isolates - Mingchao Li; Li Zhang; Zixiu Liu; Li Zhang; Runlin Xing; Songjiang Yin; Xiaochen Li; Nongshan Zhang; Peimin Wang (Hindawi Limited, 2021)
Synovitis is the primary driving factor for the occurrence and development of knee osteoarthritis (KOA) and fibroblast-like synoviocytes (FLSs) and plays a crucial role during this process. Our previous works revealed that transient receptor potential ankyrin 1 (TRPA1) ion channels mediate the amplification of KOA synovitis. In recent years, essential oils have been proved to have blocking effect on transient receptor potential channels. Meanwhile, the therapeutic effect of Sanse Powder on KOA synovitis has been confirmed in clinical trials and basic studies; although, the mechanism remains unclear. In the present study, Sanse Powder essential oil nanoemulsion (SP-NEs) was prepared, and then chemical composition, physicochemical properties, and stability were investigated. Besides, both in MIA-induced KOA rats and in LPS-stimulated FLSs, we investigated whether SP-NES could alleviate KOA synovitis by interfering with AMP-activated protein kinase- (AMPK-) mammalian target of rapamycin (mTOR), an energy sensing pathway proved to negatively regulate the TRPA1. Our research shows that the top three substances in SP-NEs were tumerone, delta-cadinene, and Ar-tumerone, which accounted for 51.62% of the total, and should be considered as the main pharmacodynamic ingredient. Less inflammatory cell infiltration and type I collagen deposition were found in the synovial tissue of KOA rats treated with SP-NEs, as well as the downregulated expressions of interleukin (IL)-1β, IL-18, and TRPA1. Besides, SP-NEs increased the phosphorylation level of AMPK and decreased the phosphorylation level of mTOR in the KOA model, and SP-NEs also upregulated expressions of peroxisome proliferator-activated receptor-gamma (PPARγ) and PPARγ coactivator-1α and downstream signaling molecules of AMPK-mTOR in vivo and in vitro. To conclude, a kind of Chinese herbal medicine for external use which is effective in treating synovitis of KOA was extracted and prepared into essential oil nanoemulsion with stable properties in the present study. It may alleviate synovitis in experimental KOA through the negative regulation of TRPA1 by AMPK-mTOR signaling.